S.A.G.E Center a smart care hospital for geriatric empowerment through gerontechnology - Gelicame, Tina Anika D.; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
"Die young as late as possible" - Dr. Miguel Ramos

Aging is a shared journey that transforms individuals and societies, requiring proactive measures to ensure dignity and well-being in later years. With the Philippines set to become an aging society by 2030, the Longitudinal Study of Aging and Health in the Philippines (LSAHP) report emphasizes the critical role of older persons (OPs) in building inclusive and resilient communities, which is also underscored by the Sustainable Development Goals 2030 and national healthcare reforms and laws. However, the country faces significant gaps: the absence of government-run geriatric centers, a shortage of geriatric healthcare personnel, and a lack of facilities designed to address the unique needs of an aging population. This architectural thesis proposes a Geriatric Center in Cebu, addressing these challenges by integrating innovative design, smart technologies, and sustainable practices. The facility adopts Smart Architecture principles to provide holistic care, prioritizing physical, mental, and emotional well-being. Smart architecture, powered by IoT and gerontechnology, ensures patient safety, operational and energy efficiency, and personalized care through advanced automation systems. This thesis demonstrates how architecture can redefine older person's care, transforming traditional institutions into inclusive, efficient, and sustainable environments. By addressing the urgent need for geriatric facilities, it aims to set a precedent for how the Philippines can support its aging population, ensuring they live meaningful, comfortable lives while contributing to a sustainable future.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Geriatric facilities -- Cebu; Health facilities -- Cebu; Geriatrics -- Cebu; Older people -- Cebu